Associations between the timing of different foods’ consumption with cardiovascular disease and all-cause mortality among adults with sleep disorders - Zhang, Jia; Zhang, Yuntao; Liu, Lin; Wang, Xuanyang; Xu, Xiaoqing; Li, Ying; Han, Tianshu; Wei, Wei (Frontiers in Nutrition, 2022)
Introduction People with sleep disorders are under disrupted biological rhythms. Whether changing the timing of specific food consumption contributes to decreasing cardiovascular and all-cause risk is unknown. Methods A total of 8,005 participants with sleep disorders were selected from the U.S. National Health and Nutrition Examination Survey (NHANES) from 2005 to 2014. Cox proportional hazards regression models were used to analyze the relationship between the consumption time of foods and cardiovascular disease (CVD) and all-cause death. Moreover, equivalent food substitution models were carried out to evaluate the alterations in the risk of CVD mortality for the changed food intake time. Results After adjusting for multiple confounders, participants who consume red and orange vegetables, starchy vegetables, and fermented dairy in the morning (hazard ratio (HR)red and orange vegetables = 0.45, 95% CI: 0.26–0.81; HRstarchy vegetables = 0.47, 95% CI: 0.25–0.88; HRfermented dairy = 0.57, 95% CI: 0.36–0.89) and milk and eggs in the evening contribute to reducing the likelihood of death from CVD (HRmilk = 0.65, 95% CI: 0.43–0.96; HReggs = 0.72, 95% CI: 0.53–0.98). Iso-calorically switching 0.1 serving of starchy vegetable and fermented dairy and milk intake from one period to another does significantly reduce the mortality risk of CVD. Conclusion Higher intake of red and orange vegetables, starchy vegetables, and fermented dairy in the morning and milk and eggs in the evening confers a lower risk of CVD among individuals with sleep disorders.